Que fizeram "ellas"? : as filhas de Maria e a boa imprensa no recife, 1902-1922 - Amaral, Walter Valdevino do (2010)
Our study, WHAT ARE THEY DOING? The Daughters of Mary and the Good Press in Recife, 1902-1922, analyzes the participation of the young members of the Pious Union of the Daughters of Mary, in the catholic press during the two first decades of the Twenty- First Century in Recife. The activity of the Daughters of Mary interests the Sciences of Religion because while defending and propagating conservative religious structures as well as good customs and family life, they were also engaged in modern activities in the participation in the catholic press. In this analysis we establish the relation between the part (an association) and the whole (society). Using the idea of habitus of Pierre Bourdieu and the concept of discipline from Michel Foucault, we analyze specific documents of the Pious Union of the Daughters of May as well as those referring to society at large. This gives us a better comprehension of the structures of the Pious Union and the activity of their members in the press. In conclusion, we show that the presence of the Daughters of Mary in the press was a victory for them due to examples of their life and devotion as well as their efforts in the propagation the good press in this period